Anion Analysis of Ionic Liquids and Ionic Liquid Purity Assessment by Ion Chromatography. Issue 1 (12th January 2017) - Rutz, Christina; Schmolke, Laura; Gvilava, Vasily; Janiak, Christoph
Abstract : The simultaneous determination of halide impurities (fluoride, chloride, bromide, and iodide) and ionic liquid (IL) anions (tetrafluoroborate, hexafluorophosphate, and triflimide) using ion chromatography was developed with a basic, non‐gradient ion chromatography system. The non‐gradient method uses the eluent Na2 CO3 /NaHCO3 in water/acetonitrile (70:30 v:v) on the AS 22 column to enable a rapid and simultaneous analysis of different IL and halide anions within an acceptable run‐time (22 min) and with good resolution R of larger than 2.4, a capacity k ′ between 0.4 and 5.1, selectivities α between 1.3 and 2.1, and peak asymmetries As of less than 1.5. Halide impurities below 1 ppm (1 mg· L –1 of prepared sample solution) could be quantified. A range of ionic liquids with tetrafluoroborate [BF4 ] –, hexafluorophosphate [PF6 ] –, and bis(trifluoromethylsulfonyl)imide (triflimide) [NTf2 ] – anions combined with cations based on imidazole, pyridine, and tetrahydrothiophene could be analyzed for their anion purity. The IL‐cations do not influence the chromatographic results. With the analysis of 18 ILs differing in their cation‐anion combination we could prove the general applicability of the described method for the anion purity analysis of ionic liquids with respect to halide ions. The IL‐anion purity of most ILs was above 98 wt %. The highest IL‐anion purity was 99.8 wt %, implying anion impurities of only 0.2 wt %. The used halide anion from the synthesis route was the major anion impurity, yet with chloride also bromide and fluoride (potentially from hydrolysis of [BF4 ] – ) were often detected. When iodide was used, at least chloride but sometimes also bromide and fluoride was present. However, even if the IL‐anion content is above 99 wt %, it does not necessarily indicate an ionic liquid devoid of other impurities. From the IC analysis, one can also deduce a possible cation impurity if one takes into account the expected (calculated) IL‐anion content. A matching experimental and theoretical IL‐anion content excludes, a higher experimental content indicates the presence of residual KBF4, NH4 PF6, or LiNTf2 salt from the halide to IL‐anion exchange. Abstract :